2014
DOI: 10.4028/www.scientific.net/amr.897.188
|View full text |Cite
|
Sign up to set email alerts
|

Basic and Hygric Properties of Concrete Containing Fine Ceramic Powder

Abstract: The motivation for utilization of active admixtures in concrete lies primarily in a positive effect on properties of hardened concrete with regard to its durability. Fine parts complement the grain size distribution curve, but also due to subsequent hydration arise phases with better resistance to aggressive substances from surrounding environment. Process of pozzolanic reaction is also associated with a reduction in open capillary porosity, causing a gradual reduction of the permeability of concrete. The pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 3 publications
0
21
0
Order By: Relevance
“…This fact, however, should not be considered as the most significant, since comparing cementitious ceramics with only marble residue and only with clay residue, resulted in that the 100mable composition has lower density, a greater porosity, and less waster absorption. This fact, attributed to the nature of the unstabilized clay particles that absorb and eliminate water easily, prove that capillary phenomena do not occur solely due to porosity 69,70 . The results of water absorption by capillarity, illustrated in Figure 6, are directly related to open porosity, shown in Table 5.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…This fact, however, should not be considered as the most significant, since comparing cementitious ceramics with only marble residue and only with clay residue, resulted in that the 100mable composition has lower density, a greater porosity, and less waster absorption. This fact, attributed to the nature of the unstabilized clay particles that absorb and eliminate water easily, prove that capillary phenomena do not occur solely due to porosity 69,70 . The results of water absorption by capillarity, illustrated in Figure 6, are directly related to open porosity, shown in Table 5.…”
Section: Resultsmentioning
confidence: 77%
“…This fact, attributed to the nature of the unstabilized clay particles that absorb and eliminate water easily, prove that capillary phenomena do not occur solely due to porosity. 69,70 The results of water absorption by capillarity, illustrated in Figure 6, are directly related to open porosity, shown in Table 5. It appears that the greater the water absorption by capillarity, the greater the open porosity established by MIP.…”
Section: Hardened State Resultsmentioning
confidence: 99%
“…Regarding the specific application of ceramic waste as a pozzolan material to act as OPC for structural concrete, Table 1 presents main works on this subject. A wide variation in the type of waste and related composition are highlighted in these works [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of CWP as partial replacement of cement attracted the attention of several researchers [6,[23][24][25][26][27][28][29][30][31][32][33][34][35]. The main conclusion from the studies was that CWP showed slow pozzolanic activity which was evidenced at late ages.…”
Section: Introductionmentioning
confidence: 99%